2018
DOI: 10.1101/496737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anchorene is an endogenous diapocarotenoid required for anchor root formation in Arabidopsis

Abstract: Arabidopsis root development is predicted to be regulated by yet unidentified carotenoidderived metabolite(s). In this work, we screened known and putative carotenoid cleavage products and identified anchorene, a predicted carotenoid-derived dialdehyde (diapocarotenoid) that triggers anchor root development. Anchor roots are the least characterized type of root in Arabidopsis. They form at the root-shoot junction, particularly upon damage to the root apical meristem. Using Arabidopsis reporter lines, mutants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 49 publications
(67 reference statements)
0
20
0
Order By: Relevance
“…Recently, Jia et al established a screening system to identify known and predicted diapocarotenoids involved in plant development, by assaying alterations in Arabidopsis roots. This approach led to the discovery of the presumed diapocarotenoid anchorene as a novel carotenoid-derived bioactive that promotes the development of anchor roots (ANRs) (Jia et al, 2019a), a less investigated type of Arabidopsis roots, which develop from the collet region situated at the root hypocotyl junction (Lucas et al, 2011). Although it is still unclear how it is formed, anchorene (C 10 ) is a natural metabolite, as confirmed by LC-MS analysis (Jia et al, 2019a; Mi et al, 2019a), and its structure indicates that it can be produced by cleaving the (C11–C12) and (C11′–C12′) double bound from all carotenoids downstream of ζ-carotene in the carotenoid biosynthesis pathway ( Figure 5B ).…”
Section: Novel Carotenoid-derived Signaling Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Jia et al established a screening system to identify known and predicted diapocarotenoids involved in plant development, by assaying alterations in Arabidopsis roots. This approach led to the discovery of the presumed diapocarotenoid anchorene as a novel carotenoid-derived bioactive that promotes the development of anchor roots (ANRs) (Jia et al, 2019a), a less investigated type of Arabidopsis roots, which develop from the collet region situated at the root hypocotyl junction (Lucas et al, 2011). Although it is still unclear how it is formed, anchorene (C 10 ) is a natural metabolite, as confirmed by LC-MS analysis (Jia et al, 2019a; Mi et al, 2019a), and its structure indicates that it can be produced by cleaving the (C11–C12) and (C11′–C12′) double bound from all carotenoids downstream of ζ-carotene in the carotenoid biosynthesis pathway ( Figure 5B ).…”
Section: Novel Carotenoid-derived Signaling Moleculesmentioning
confidence: 99%
“…In Arabidopsis , application of anchorene induces ANR formation. The regulation of ANR by anchorene is highly specific to its chemical structure, as application of a structural isomer did not show an effect on ANR development, and altering anchorene functional group(s) to alcohol, acid, or acid-ethyl ester resulted in a loss of activity (Jia et al, 2019a). The usage of auxin reporter lines and an auxin transport inhibitor, together with transcriptome analysis, showed that anchorene’s effect on ANR development is caused by modulating auxin homeostasis.…”
Section: Novel Carotenoid-derived Signaling Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it was very recently reported that anchorene, a C 10 DIAL, is a signaling molecule that regulates root development in Arabidopsis and rice. 13 In addition, studies on rosafluene, a C 14 DIAL, and its structural isomer demonstrated that they inhibit the activity of nuclear factor kappa B in bone and cancer cells and reduce the growth of breast and prostate cancer cells. 21 , 22 These results indicate the importance of DIALs for nutrition and plant science.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the class of carotenoid-derivatives includes hormones, such as abscisic acid and strigolactone, [18][19][20][21][22][23][24][25], retinoids, i.e. retinal, retinol (vitamin A), and retinoic acid [26][27][28], the fungal pheromone trisporic acid [29,30], the stress signaling molecule β-cyclocitral [31][32][33], the recently discovered growth regulators anchorene and zaxinone [34,35], pigments, such as crocin in saffron [36], citraurin in citrus fruits [37], and the fungal neurosporaxanthin [38,39], and volatiles, such as safranal [40,41], geranial [42] and β-ionone [43,44]. All of these bioactive metabolites (named apocarotenoids) are generated by oxidative cleavage of carotenoids, which is generally catalyzed by carotenoid cleavage dioxygenases (CCDs) or by nonenzymatic oxidation caused by reactive oxygen species (ROSs) [25,32,45,46].…”
Section: Introductionmentioning
confidence: 99%